1995
DOI: 10.21273/hortsci.30.3.647
|View full text |Cite
|
Sign up to set email alerts
|

`Equinox' Heat-tolerant Hybrid Tomato

Abstract: results in more reliable marketable fruit production during cooler cropping seasons. Origin 'Equinox' was tested as Fla. 7249B and is a hybrid resulting from the Fla. 7324 x Fla. 7060 cross. The pollen parent was tested as Fla. 7249B (Fig. 1). Fla. 7060 also was the pollen parent in 'Solar Set', and its background has been described by Scott et al. (1989). Fl. 7060 was the seed parent cited in the release circular, but subsequently the parentage was reversed due to germination sensitivity in Fla. 7060, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A number of studies have assessed tomato cultivars for fruit set under CMH condition and identified relatively well-performing genotypes (Levy et al 1978 ; Dane et al 1991 ; Sato et al 2000 ; Sato et al 2004 ; Bhattarai et al 2016 ). The largest, multi-year characterisations by the Asian Vegetable Research and Development Center (AVRDC) identified 39 tolerant lines, some of which have already been utilised in tomato breeding programs (Opeña et al 1992 ; Scott et al 1995 ; Gardner 2000 ). However, to be able to efficiently use variation in heat tolerance for fundamental and applied aims, it is necessary to have knowledge on the genetic basis of the trait.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have assessed tomato cultivars for fruit set under CMH condition and identified relatively well-performing genotypes (Levy et al 1978 ; Dane et al 1991 ; Sato et al 2000 ; Sato et al 2004 ; Bhattarai et al 2016 ). The largest, multi-year characterisations by the Asian Vegetable Research and Development Center (AVRDC) identified 39 tolerant lines, some of which have already been utilised in tomato breeding programs (Opeña et al 1992 ; Scott et al 1995 ; Gardner 2000 ). However, to be able to efficiently use variation in heat tolerance for fundamental and applied aims, it is necessary to have knowledge on the genetic basis of the trait.…”
Section: Introductionmentioning
confidence: 99%
“…These species, which are mostly self incompatible and produce green fruit, have been rather partial in their usefulness to cultivated forms due to various barriers present in sexual hybridization and gene transfer. However, they can be hybridized with members of the esculentum complex by the application of techniques such as embryo rescue [ 23 , 24 , 32 ] or by the use of pollen mixtue (with tomato pollen) when fertilizing tomato plants [ 33 ]. There are documented examples of crosses with peruvianum complex which have been utilized in tomato breeding, including transfer of tobacco mosaic virus and nematode resistance [ 30 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is unfortunate that the literature contains relatively little information on breeding for heat tolerance in different crop species. However, despite all the complexity of heat tolerance and difficulties encountered during transfer of tolerance, some heat-tolerant inbred lines and hybrid cultivars with commercial acceptability have been developed and released, at least in a few crop species such as tomato (Scott et al, 1986(Scott et al, , 1995. Composite interval mapping (CIM) has been used in the present investigation for mapping QTLs associated with heat tolerance using pooled bulks from the F 2 population of Ksu106 (heat tolerant)/Yecora Rojo (heat-sensitive) cross.…”
Section: Discussionmentioning
confidence: 99%